8.1k views
3 votes
Solve the equation for y.
6 = 4x +9y

User Jerdak
by
4.2k points

2 Answers

5 votes

Answer:

y = 2/3 - 4x/9

Explanation:

6 = 4x + 9y

you have to isolate the 9y soo, subtract 4x on both sides

6 - 4x = 9y

now, divide both sides by 9

6/9 - 4x/9 = y

simplify!

2/3 - 4x/9 = y

User Samg
by
5.5k points
4 votes

Answer:

y = (6-4x) / 9

Explanation:

6 = 4x+9y

Subtracting 4x to both sides

6 - 4x = 9y

Now dividing both sides by 9

We'll get

(6-4x)/9 = y

OR

y = (6-4x) / 9

User Luke Xu
by
5.2k points